Lifestyle segmentation: mobile phone purchase vis-à-vis consumption decision - Nugraha, Albert Kriestian Novi Adhi; Silintowe, Yunita Budi Rahayu; Paramita, Eristia Lidia (Business: Theory and Practice, 2022)
Prior studies intensively rely on lifestyle segmentation to investigate the patterns of purchase and consumption decisions. However, the literature does not specifically relate lifestyle profiles with the types of consumer decisions (i.e., purchasing vs. consumption decisions). Therefore, this research analyzed the issue by surveying 626 residents of Salatiga city, Indonesia, as the participants through self-administered questionnaires. By analyzing the data with factor, cluster, and chi-square analysis, this paper demonstrated that purchase decisions (i.e., the choice of brand name and country of origin) are not associated with lifestyle segments, while consumption decisions differ among the segments. Meanwhile, lifestyle is more likely associated with enduring (i.e., consumption decisions) than occasional behaviors (i.e., purchase decisions) such as the purchase of a mobile phone and its related services.